Traffic Performance Analysis of Angkatan 66 Intersection, Palembang City, Following Flyover Operation - Wahiputra, Muhammad Rafiq; Arliansyah, Joni; Della, Rhaptyalyani Herno (Jurnal Teknik Sipil, 2025)
This study evaluates the impact of the Flyover Bridge operation at the Angkatan 66 Intersection in Palembang City on traffic performance, road network conditions, and environmental emissions. The research involved geometric surveys, traffic volume analysis, and traffic signal evaluations, followed by performance simulations using PTV VISSIM, PTV VISUM, and EnViVer programs. The findings indicate that the flyover significantly improved traffic conditions by reducing queue lengths and vehicle delays by 88% and 71%, respectively. Furthermore, traffic signal cycle times became shorter, enhancing intersection efficiency. However, road and intersection performance projections for the next decade indicate a gradual increase in average traffic volumes, vehicle queues, and delays, reflecting growing traffic demand that will congest roads and intersections near the site without further development. The study also found substantial reductions in vehicle emissions, including COâ‚‚, NOâ‚“, and PMâ‚â‚€, after the flyover began operation. These outcomes confirm the flyover"™s effectiveness in alleviating congestion and improving air quality. Nevertheless, proactive measures are recommended to maintain long-term traffic efficiency. The study contributes valuable insights for sustainable urban transportation planning and civil engineering practices.